1989
DOI: 10.1063/1.857514
|View full text |Cite
|
Sign up to set email alerts
|

Negative nonlinearity in selected fluorocarbons

Abstract: Modelling of electronic excitation and radiation in the Direct Simulation Monte Carlo Macroscopic Chemistry Method Phys. Fluids 24, 106102 (2012) Molecular dynamics simulation of rotational relaxation in nitrogen: Implications for rotational collision number models Phys. Fluids 24, 106101 (2012) One-dimensional plate impact experiments on the cyclotetramethylene tetranitramine (HMX) based explosive EDC32 J. Appl. Phys. 112, 064910 (2012) Slightly two-or three-dimensional self-similar solutions Phys. Fluids 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 9 publications
4
53
0
Order By: Relevance
“…32 Yet the interpretation of the results presented in Refs. 5 and 32 has been challenged by Cramer, 33 Thompson, 29 Fergason et al 34,35 and the observed wavefield is now believed to be related to both critical point and two-phase nonclassical effects.…”
Section: Introductionmentioning
confidence: 99%
“…32 Yet the interpretation of the results presented in Refs. 5 and 32 has been challenged by Cramer, 33 Thompson, 29 Fergason et al 34,35 and the observed wavefield is now believed to be related to both critical point and two-phase nonclassical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the pioneering work of Lambrakis and Thompson, 21 many studies [22][23][24][25] relied upon various thermodynamic models to compute the value of ⌫ for several commercially available fluids in order to identify the most promising ones for both applications and experiments. The fluids under investigation were organic compounds and belong to the class of the alkanes, the ethers, the perfluorocarbons, and the siloxanes.…”
Section: Introductionmentioning
confidence: 99%
“…These complex equations, whose accuracy in computing the value of Γ has been discussed by Colonna et al (under review), have been applied to the selected linear and cyclic siloxane and perfluorocabons fluids listed in table 1, where relevant thermophysical properties are also reported for the reader's convenience. Additional information on the thermophysical properties of these fluids and their gasdynamic behaviour can be found in Nannan et al (2007) and Colonna et al ( , 2008b for siloxanes and Lambrakis & Thompson (1972), Cramer (1989Cramer ( , 1991 and Guardone & Argrow (2005) for perfluorocarbons. The minimum value of Γ obtained from the three thermodynamic models is also reported.…”
Section: Results For Selected Siloxanes and Perfluorocarbonsmentioning
confidence: 99%
“…These complex models include various thermophysical parameters, such as the acentric factor ω, in their functional forms, and therefore the number of active degrees of freedom, N, no longer represents molecular complexity, as discussed by Guardone & Argrow (2005). Therefore, the minimum value of the fundamental derivative in the vapour phase, Γ min , which occurs at a state point along the VLE line, is used in the following Stewart, Jacobsen & Penocello (1969), Lambrakis & Thompson (1972), Cramer (1989Cramer ( , 1991, Guardone & Argrow (2005), Nannan et al (2007) and Colonna et al ( , 2008b.…”
Section: Results For Selected Siloxanes and Perfluorocarbonsmentioning
confidence: 99%